The effect of substrate temperature on the physical properties of spray pyrolysed CdS thin films - T.A. Abbas; A.O. Jafir (College of Education for Pure Sciences, 2012)
Abstract Cadmium sulphide (CdS) thin films with different substrate temperatures were prepared on glass substrates by spray pyrolysis technique. XRD patterns indicated the presence of single- phase hexagonal CdS. UV-VIS spectra of the films in the spectral region from 300 nm to 900 nm were studied using the optical transmittance measurements which were taken. The direct band gap energy of the films was found to be increasing from 2.44 to 2.45 eV with increased substrate temperature from 325 to 375 C. The electrical conductivity of the films was found to be increase as the substrate temperature. The annealing effect in air increases the dark conductivity while the activation energy decreased.